Teacher Competency Development Management Of Modern Daar Al Uluum Asahan Islamic Boarding School - Suhardi Suhardi; Syafaruddin Syafaruddin; Candra Wijaya (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
The focus of this research problem is how to manage the competency development of Madrasah Aliyah teachers at the Daar Al Uluum Asahan Modern Islamic Boarding School. While the research objectives consist of: (a) how to plan the competency development of madrasah aliyah teachers at the Daar Al Ulum Asahan Islamic Boarding School, (2) how to implement the competency development program for madrasah aliyah teachers at the Daar Al Ulum Asahan Islamic Boarding School, (3) how to implement the program competency development for madrasah aliyah teachers at the Daar Al Ulum Asahan Islamic boarding school, and (4) How is the implementation of the aliyah madrasa teacher competency development program at the Daar Al Ulum Asahan Islamic boarding school. This study used a qualitative approach with a descriptive method which aims to determine the planning, preparation, program implementation, and evaluation of teacher competency development. Data collection techniques using interviews, observation and document study. While the data analysis techniques use procedures; data reduction, data exposure, and conclusion drawing. To strengthen the validity of data analysis and research findings, researchers refer to the use of data validity standards suggested by Lincoln & Guba, which consist of credibility, transferability, dependability and comfirmability. (1, Planning for competency development for Madrasah Aliyah teachers at Daar al Ulum Asahan Islamic Boarding School is carried out with Madrasah Aliyah work meetings as a decision-making process in determining plans to be carried out every year. (2, Implementation of teacher competency development programs through two programs, namely informal development programs where teachers increase their competence by studying various book sources to increase knowledge, and attend various kinds of training to develop their competence (3, Organizing the development of madrasah aliyah teachers at Daar Al Ulum Asahan is the responsibility of the pesantren leadership, even though the madrasa head is the operational executor of teacher competency development (4. Supervision of the madrasah teacher competency development program at the Daar Al Ulum Asahan Islamic boarding school is carried out by submitting oral reports and written reports. In the practice of fostering teacher competency development orally, the head of the activity committee together with the head of the madrasa after completing the activity reports verbally on the implementation of the activity , and after that within two weeks a written report is given.